2009
DOI: 10.1124/jpet.109.160564
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Pharmacokinetics of Glyburide, Rhodamine 123, and BODIPY FL Prazosin: Effect of Drug Efflux Transporters and Lipid Solubility

Abstract: Breast cancer resistance protein (BCRP) and P-glycoprotein (P-gp) are the most abundantly expressed ATP-binding cassette (ABC) drug transporters in the placenta. They recognize a large, partly overlapping spectrum of chemically unrelated compounds and affect their transplacental passage. In this study we investigate the effect of Bcrp and P-gp on the transplacental pharmacokinetics of their specific and common substrates employing the technique of dually perfused rat placenta. We show that the clearance of rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 41 publications
2
25
1
Order By: Relevance
“…Using this approach, we have previously identified ABC transporter-mediated placental passage of several compounds, including antiretrovirals (25,26,32,41). In the present study, we showed that the fetal-to-maternal clearance of lamivudine was not significantly higher than the maternal-to-fetal clearance and that the decrease of lamivudine concentration in fetal compartment during the recirculation experiment was insignificant (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Using this approach, we have previously identified ABC transporter-mediated placental passage of several compounds, including antiretrovirals (25,26,32,41). In the present study, we showed that the fetal-to-maternal clearance of lamivudine was not significantly higher than the maternal-to-fetal clearance and that the decrease of lamivudine concentration in fetal compartment during the recirculation experiment was insignificant (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…To confirm our in-vitro findings on the organ level, we employed the method of dually perfused rat term placenta, a well established method to study placental pharmacology [23,24,32,33] and physiology [34,35]. As both rat and human placenta express abundant amounts of ABCB1 [9] and ABCG2 [10], we introduced this model as a suitable tool to investigate the role of placental ABCB1 [33] and ABCG2 [23] in placental disposition of drugs.…”
Section: Discussionmentioning
confidence: 52%
“…This experimental setup ensures steady concentration on the maternal side of the placenta and enables investigation of fetal/maternal ratio; any net transfer of the substrate implies transport against a concentration gradient and provides evidence of active transport. To determine the effect of efflux transporters on placental passage of TDF, GF120918 (2 mmol/l), a dual inhibitor of ABCB1 and ABCG2 [24], or indomethacin (0.28 mmol/l), a nonspecific inhibitor of ABCCs [25], were added to both maternal and fetal reservoirs and the fetal/maternal concentration ratio at equilibrium was calculated.…”
Section: Reagents and Chemicalsmentioning
confidence: 99%
“…The lack of interaction of abacavir with ABCB1 and ABCG2 transporters in the open-circuit experimental setup of rat placenta perfusion as well as in human placenta villous fragments could be explained by involvement of passive diffusion that lowers the effect of active transporters [34] or by concentrative/uptake transporters mediating transport abacavir across the placental membranes, e.g., nucleoside transporters CNTs and ENTs (our unpublished data) whose functional expression has recently been confirmed in both, human and rat placentas [35,36]. We therefore hypothesize that under the conditions of open-circuit setup, in which the drug is presented from one side of trophoblast layer only, the uptake and/or equilibrative transporters might mediate transplacental transfer of abacavir to the trophoblast layer and thereby hinder the efflux function of ABCB1/ABCG2 transporters in these experimental conditions.…”
Section: Discussionmentioning
confidence: 95%